Gender-stratified analyses of symptoms associated with life-threatening events in patients calling out-of-hours primary care for shortness of breath - Michelle Spek; Dorien L. Zwart; Gerardus J. H. M. Reijers; Esther de Groot; Geert-Jan Geersing; Maarten van Smeden; Hester M. den Ruijter; Anna S. M. Dobbe; Mathé Delissen; Frans H. Rutten; Roderick P. Venekamp (BMC Primary Care)
Abstract Background Women and men seem to perceive shortness of breath (SOB) differently. However, it is unknown whether symptom presentation varies between genders during a life-threatening event (LTE). Aim To assess whether symptoms associated with an LTE vary between women and men with SOB calling out-of-hours primary care (OHS-PC). Methods Cross-sectional study including data from patients contacting two large Dutch OHS-PC centres for SOB between 1 September 2020 and 31 August 2021. We compared symptoms mentioned during triage conversations between patients with and without LTEs (amongst others, acute coronary syndrome, pulmonary embolism, acute heart failure and severe pneumonia), stratified by gender. Results We included 1,861 adults contacting OHS-PC for SOB (mean age 53.3 years, 55.3% women). The risk of an LTE was lower in women than in men (15.0% vs. 18.7%, RR 0.80; 95% CI 0.65–0.98). Patients with LTEs were older, more often had someone else calling for them, a history of cardiovascular disease, cardiovascular medication use and inability to speak full sentences compared to those without LTEs. Differences between women and men were only apparent for calling at night (women: 24.0% vs. 15.2%, p = 0.006, versus men: 18.7% vs. 22.5%, p = 0.300; p-value interaction term: 0.009) and participation of general practitioners during telephone triage (women: 49.4% vs. 49.5%, p = 0.975, versus men: 56.1% vs. 43.0%, p = 0.003; p-value interaction term: 0.033). Conclusions Among patients contacting OHS-PC with SOB, about 1 in 6 had an LTE, more often men than women. We found no strong evidence of symptom differences between gender groups predictive of LTEs. Trial registration The Netherlands Trial Register, number: NL9682, registration date: 20–08-2021.